Application of The Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) Method in Zinc Analysis - Nabilah Bilqis; Erni Sulistiawati; Miftakh Nur Rahman (Universitas Nusa Bangsa, 2022)
Zinc is a nutrient that affects cell growth, helps the body's metabolism, activates T cells (T lymphocytes), cell regeneration, and repairs body tissues. Zinc in the body undergoes a process of excretion every day, therefore daily intake of zinc needs to be considered to maintain the amount of zinc in the body in a normal amount. This study aimed to obtain information on the application of the Inductively coupled plasma-mass spectrometry (ICP-MS) method to determine the concentration of zinc in the serum of pregnant women. The application of Inductively coupled plasma-mass spectrometry (ICP-MS) method in zinc analysis provided the advantages of a minimal sample volume requirement with higher instrument sensitivity, fast retention time and had a concentration detection limit of up to parts per billion (ppb). Analysis of the zinc concentration in the serum of pregnant women using the ICP-MS method showed 80% serum with a concentration below the reference value, 13.3% normal and 6.7% a concentration higher than the WHO reference value.Keywords:Â defisiensi zink,Â inductively coupled plasma-mass spectrometry (icp-ms),Â zinkAplikasi Metode Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) Dalam Analisis ZinkABSTRAKZink adalah salah satu jenis zat gizi yang sangat berpengaruh terhadap pertumbuhan sel, mengaktifkan sel T (limfosit T), regenerasi sel, dan membantu metabolisme tubuh. Zink di dalam tubuh setiap harinya mengalami proses ekskresi oleh karena itu asupan harian zink perlu diperhatikan untuk menjaga jumlah zink di dalam tubuh tetap dalam jumlah yang normal. Penelitian ini bertujuan untuk mendapatkan informasi penggunaan metode Inductively coupled plasma-mass spectrometry (ICP-MS) untuk menentukan konsentrasi zink dalam serum ibu hamil. Penggunaan metode ICP-MS dalam analisis zink memberikan keuntungan berupa kebutuhan volume sampel minimal dengan sensitivitas alat lebih tinggi, waktu retensi yang cepat serta memiliki batas limit deteksi konsentrasi hingga bagian per triliun (ppt). Analisis konsentrasi zink dalam serum ibu hamil dengan metode ICP-MS menunjukan 80% serum dengan konsentrasi dibawah nilai rujukan, 13,3% normal dan 6,7% konsentrasi yang lebih tinggi dibandingkan nilai rujukan menurut WHO.Kata kunci : defisiensi zink, inductively coupled plasma-mass spectrometry (icp-ms), zink